Republic of Turkey Gas Complex Development: Problems and Prospects - Khalova, Gul'nar Osmanovna; Sopilko, Natalya Yuryevna; Illeritsky, Nikita Igorevich (International Journal of Energy Economics and Policy, 2018)
Turkey is a large, populated and dynamically developing state with growing energy demand. Yet it faces several issues concerning the development of the national energy sector, i.e. energy supply diversity and CO2 emissions reduction. Natural gas may be a suitable kind of fuel to ensure better development for the Turkish energy sector. Moreover, Turkey plays an important role as a transit country for natural gas supplies and in the future, it can become one of the key gas hubs in the south-eastern part of Europe, as it occupies a strategically advantageous geographical position at the junction of Europe and Asia. However, the existing Turkish natural gas pipeline transmission and storage system have a relatively low capacity, insufficient for natural gas large volumes transit. In addition, natural gas supplies from Azerbaijan and Iran are not reliable enough. This paper reviews the main economic development and energy sector indicators of Turkey, along with current and future natural gas supply and transit projects. The recommendations for natural gas sector development and further energy cooperation with Russia are provided. Keywords: Natural Gas, Turkey, Russia, Europe, Energy Supply, Energy Cooperation, Natural Gas Pipelines, Blue Stream, Turkish Stream, TANAP JEL Classifications: Q4, Q41 DOI: https://doi.org/10.32479/ijeep.7344